1985
DOI: 10.1038/316163a0
|View full text |Cite
|
Sign up to set email alerts
|

An enhancer-like sequence within the Xenopus U2 gene promoter facilitates the formation of stable transcription complexes

Abstract: Enhancers are eukaryotic promoter elements that increase transcriptional efficiency in a manner relatively independent of their position and orientation with respect to a nearby gene. There is growing evidence that enhancer action is mediated by transacting factors, but the mode of action of these factors is not yet known. We report here on the Xenopus U2 gene promoter, which contains two sequence elements. The distal sequence element increases promoter activity 20-fold by facilitating the formation of stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
202
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(213 citation statements)
references
References 26 publications
11
202
0
Order By: Relevance
“…However, when 10 393 Figure 2A and B, the sequence 5'-ATGCAAA-3' homologous to the immunoglobulin heavy chain enhancer (position 212 -206) is underlined, and the polyoma virus enhancer homology (P-motif, position 196-186) is boxed. References for the various sequence elements are as follows (see also text): LPV enhancer (Pawlita et al, 1985;Mosthaf et al, 1985); BK virus (BKV) enhancer (Rosenthal et al, 1983); Igx light chain enhancer (Picard and Schaffner, 1984;Queen and Stafford, 1984); consensus sequences of the upstream promoter elements of the immunoglobulin heavy (VH) and light (VL, opposite strand) chain genes (Falkner and Zachau, 1984;Parslow et al, 1984); Ig heavy chain enhancer (opposite strand, Ephrussi et al, 1985 and references therein; the star indicates the C complementary to the G protected against dimethylsulfate modification, see text); Xenopus Ul/U2 RNA genes (Mattaj et al, 1985;Ciiberto et al, 1985;Krol et al, 1985); polyoma virus enhancer (opposite strand, Veldman et al, 1985;Ruley and Fried, 1983). For comparison the ElA-like motif of the polyoma virus enhancer (Hearing and Shenk, 1983;Herbomel et al 1984) is shown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when 10 393 Figure 2A and B, the sequence 5'-ATGCAAA-3' homologous to the immunoglobulin heavy chain enhancer (position 212 -206) is underlined, and the polyoma virus enhancer homology (P-motif, position 196-186) is boxed. References for the various sequence elements are as follows (see also text): LPV enhancer (Pawlita et al, 1985;Mosthaf et al, 1985); BK virus (BKV) enhancer (Rosenthal et al, 1983); Igx light chain enhancer (Picard and Schaffner, 1984;Queen and Stafford, 1984); consensus sequences of the upstream promoter elements of the immunoglobulin heavy (VH) and light (VL, opposite strand) chain genes (Falkner and Zachau, 1984;Parslow et al, 1984); Ig heavy chain enhancer (opposite strand, Ephrussi et al, 1985 and references therein; the star indicates the C complementary to the G protected against dimethylsulfate modification, see text); Xenopus Ul/U2 RNA genes (Mattaj et al, 1985;Ciiberto et al, 1985;Krol et al, 1985); polyoma virus enhancer (opposite strand, Veldman et al, 1985;Ruley and Fried, 1983). For comparison the ElA-like motif of the polyoma virus enhancer (Hearing and Shenk, 1983;Herbomel et al 1984) is shown.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the juxtaposition of the two Sph-motifs in the SV40 enhancer generates a sequence element which is present in the immunoglobulin heavy chain enhancer (Banerji et al, 1983;Gilles et al, 1983;Neuberger, 1983) and in the upstream elements of the promoters of the VH and VL immunoglobulin genes (Falkner and Zachau, 1984;Parslow et al, 1984) (Figure 6). A homologous motif, which exhibits enhancer properties (Mattaj et al, 1985), has also been described in a conserved sequence of a distal element of the Xenopus Ul and U2 RNA genes (Mattaj et al, 1985;Ciliberto et al, 1985;Krol et al, 1985). It is interesting to note that the G residue complementary to the C present in this sequence in the immunoglobulin heavy chain enhancer (see Figure 6) is protected against dimethylsulfate methylation in lymphoid B cells, but not in other cell lines, which suggests that this sequence interacts with a protein specifically in lymphoid B cells (Ephrussi et al, 1985).…”
Section: Discussion 7he Sv40 Enhancer Domainsmentioning
confidence: 99%
“…The frog U2 gene contains an enhancer-like element (Mattaj et al 1985) that is nearly identical in sequence to the human U2 enhancer over the region where Spl and NF-A bind to the human enhancer ( Figs. 2-4; see Ares et al 1985).…”
Section: Is a Protein-protein Interaction Between Spl And Nf-a A Specmentioning
confidence: 99%
“…A 4-bp deletion in the octamer of the human U2 gene abolishes U2 enhancer activity (Ares et al 1985;Mangin et al 1986) and the human U2 gene can compete with the histone H2B promoter for binding of NF-A1 (Sire and Roeder 1986). In addition, a synthetic oligonucleotide containing an octamer sequence can partly replace the frog U2 enhancer (Mattaj et al 1985).…”
mentioning
confidence: 99%
“…The octamer site is also important for transcription of the snRNA genes although their expression is not restricted to lymphoid cells (Mattaj et al, 1985;Ares et al, 1987;Ciliberto et al, 1987;Janson et al, 1987Janson et al, , 1989Dahlberg and Schenborn, 1988;Tanaka et al, 1988). Transcription of human U2 genes is controlled by a proximal sequence element (PSE) and a distal sequence element (DSE) which is also called the U2 enhancer (Westin et al, 1984;Ares et al, 1985;Mangin et al, 1986; for review see Dahlberg and Lund, 1987).…”
Section: Introductionmentioning
confidence: 99%